Oxygen diffusion hardened zirconium alloy ZrNb7 – Tribological properties derived from Calo wear and wheel on flat experiments. (January 2022) - Mosbacher, Mike; Hilzenthaler, Marius; Galetz, Mathias; Glatzel, Uwe
Abstract: Tribological properties of oxidized ZrNb7, exposed to three different heat treatment routes, were investigated. These are: oxidation in air, a three step heat treatment process and an oxidation at low oxygen partial pressure. The latter two increase the oxygen diffusion zone below the oxide scale leading to enhanced coating adhesion. To assess tribological properties, a self-developed knee test bench was used where all three variants of ZrNb7 were compared to commercially available materials. ZrNb7 oxidized at low oxygen partial pressure shows the lowest wear, both on the ceramic surface and on the UHMWPE counterpart. In addition, the same coating exhibits better performance in Calo wear tests than the surface of martensitic hardened steel (100Cr6) as a reference material. Highlights: ZrNb7 specimens were exposed to three different heat treatment routes. Tribological testing was done on a knee test bench and with calo wear tests. Coating adhesion was tested by Rockwell indentation tests. Oxidation of ZrNb7 at low oxygen partial pressure shows the best wear resistance.